Perspective of new distributed grid connected roof top solar photovoltaic power generation policy interventions in India. (September 2022) - Chandel, Rahul; Chandel, Shyam Singh; Malik, Prashant
Abstract: The building integrated rooftop solar photovoltaic (PV) systems, contribute significantly to the decentralised power generation. In this study a detailed analysis of the new distributed power generation policy from roof top PV systems, in India, is carried out along with identifying policy interventions required for its successful implementation. A contrasting perspective of decentralised power generation analysis is presented for roof top power generation enhancement and solar industry growth in India. As a case study, the implementation of roof top PV power generation in India is presented which faces a number of challenges including resistance from energy distribution companies (DISCOMs). The electricity tariff analysis is also carried out, to suggest corrective measures. The novelty of the study is that it identifies solar tariff, benchmark cost, energy subsidy pattern, release methodology and lack of incentives to DISCOMs as crucial parameters to be addressed for roof top PV promotion. The study is of importance and of interest for the effective implementation of distributed renewable power generation in the residential sector for solar industry and DISCOM growth in India and other countries worldwide. Highlights: The distributed solar power generation policies of countries worldwide are critically analysed. A perspective of new distributed grid connected roof top solar photovoltaic system policy in India, is presented. A contrasting perspective of the new Indian policy with European and Asian countries is presented. Policy interventions for enhancing power generation from roof top systems, are identified. A strategy to enhance PV industry growth in building sector is presented.